NEW EDITION OF SOURCES ON THE HISTORY OF THE UNIATE CHURCH (The Peer-Review of the monograph: Vinnytsia Viceroyalty (Dean's Office) of the Ruska Catholic Church in the 17th Century: Research, Publication of Visitations Acts/ M.S. Hrushevsky Institute of Ukrainian Archeography and Source Studies of the National Academy of Sciences of Ukraine; State Archives of Vinnytsia Region; Vinnytsia Museum // Research by Arsen Zinchenko; Translations, Indexes, Terminological Dictionary by Oles Petrenko. Zaporizhzhia: FOP Riabtsev V.V., 2023. 896 p.: ill. [Series “Archive Key”, Part. II, Vol. 1]) - TYMOSHENKO, Leonid; BILA , Svitlana (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The Peer-Review of the monograph: Vinnytsia Viceroyalty (Dean's Office) of the Ruska Catholic Church in the 17th Century: Research, Publication of Visitations Acts/ M.S. Hrushevsky Institute of Ukrainian Archeography and Source Studies of the National Academy of Sciences of Ukraine; State Archives of Vinnytsia Region; Vinnytsia Museum // Research by Arsen Zinchenko; Translations, Indexes, Terminological Dictionary by Oles Petrenko. Zaporizhzhia: FOP Riabtsev V.V., 2023. 896 p.: ill. [Series “Archive Key”, Part. II, Vol. 1]